Association of Pregestational BMI and Gestational Weight Gain with Maternal and Neonatal Outcomes in Adolescents and Adults from Mexico City - Sámano, Reyna; Chico Barba, Laura Gabriela; Flores-Quijano, María Eugenia; Godínez-Martínez, Estela; Martínez-Rojano, Hugo; Ortiz-Hernandez, Luis; Nájera-Medina, Oralia; Hernández-Trejo, María; Hurtado-Solache, Cristopher (My University, 2021)
During pregnancy, adolescents experience physiological changes different from adults because they have not concluded their physical growth. Therefore, maternal and neonatal outcomes may not be the same. This paper aimed to analyze the association between pregestational BMI (pBMI) and gestational weight gain (GWG) with maternal and neonatal outcomes in adolescent and adult pregnant women. The authors performed an observational study that included 1112 women, where 52.6% (n = 585) were adolescents. Sociodemographic information, pBMI, GWG, neonatal anthropometric measures, and maternal and neonatal outcomes were obtained. Adolescent women had a mean lower (21.4 vs. 26.2, p ≤ 0.001) pBMI than adults and a higher gestational weight gain (12.3 vs. 10.7 kg, p ≤ 0.001). According to Poisson regression models, gestational diabetes is positively associated with insufficient GWG and with pregestational obesity. Furthermore, the probability of developing pregnancy-induced hypertension increased with pBMI of obesity compared to normal weight. Preeclampsia, anemia, and preterm birth were not associated with GWG. Insufficient GWG was a risk factor, and being overweight was a protective factor for low birth weight and small for gestational age. We conclude that pBMI, GWG, and age group were associated only with gestational diabetes and low birth weight.